2016
DOI: 10.3847/0004-637x/826/1/14
|View full text |Cite
|
Sign up to set email alerts
|

Lyman-Alpha Spectra From Multiphase Outflows, and Their Connection to Shell Models

Abstract: We perform Lyman-α (Lyα) Monte-Carlo radiative transfer calculations on a suite of 2500 models of multiphase, outflowing media, which are characterized by 14 parameters. We focus on the Lyα spectra emerging from these media, and investigate which properties are dominant in shaping the emerging Lyα profile. Multiphase models give rise to a wide variety of emerging spectra, including single, double and triple peaked spectra. We find that the dominant parameters in shaping the spectra include (i) the cloud coveri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 62 publications
0
42
0
1
Order By: Relevance
“…As a consequence, the majority of the Lyα flux is peaked in the center of the galaxy and does not produce an extended Lyα spatial profile. The models from Barnes & Haehnelt (2010) also indicate that the Lyα emission becomes more centrally peaked with the increase of the velocity of the HI bulk (see also Gronke & Dijkstra 2016).…”
Section: Theoretical Modelmentioning
confidence: 87%
See 2 more Smart Citations
“…As a consequence, the majority of the Lyα flux is peaked in the center of the galaxy and does not produce an extended Lyα spatial profile. The models from Barnes & Haehnelt (2010) also indicate that the Lyα emission becomes more centrally peaked with the increase of the velocity of the HI bulk (see also Gronke & Dijkstra 2016).…”
Section: Theoretical Modelmentioning
confidence: 87%
“…Our data do not seem to favour the presence of holes. According to Gronke & Dijkstra (2016), clumpy outflows decrease the effective optical depth seen by the Lyα photons compared to the "real" column density seen by non-resonant photons along the line of sight, and lead to a small peak shift and boosted escape fraction in comparison to a homogeneous medium of the same outflow velocity and same column density. It remains to be studied if a correlation with the spatial extension, as observed in Fig.…”
Section: Interpretation Of the Observed Small Outflow Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…2). The latter authors concluded from their observation of 91 LAEs that more than 40% of them show a double peak, and that in most cases the red component is stronger than the blue one, which is naturally explained by transfer effects in expanding media, even inhomogeneous ones (Verhamme et al , 2008(Verhamme et al , 2012Gronke & Dijkstra 2016).…”
Section: Two Other Probable Lyman Alpha Emitters At the Same Redshiftmentioning
confidence: 97%
“…Second, Gronke & Dijkstra (2016) have performed Lyα radiative transfer calculations of multiphase ISM models. The result shows that narrow Lyα profiles can be reproduced by two cases, one of which is on the condition that a galaxy has a low covering fraction of the neutral gas 4 .…”
Section: 2mentioning
confidence: 99%